Memprediksi Perilaku Penggunaan Kontrasepsi Menggunakan Theory Health Belief Model - Retno Heru Setyorini; Riadini Wahyu Utami (LPPM Hang Tuah Pekanbaru, 2022)
Although the achievement of the Modern Contraceptive Prevelance Rate in Indonesia is high, unmet need is still a target that has not been in accordance with the target that has been set. This still shows the low use of contraceptives by women of childbearing age. The purpose of this study was to determine the factors associated with the use of contraception. A cross sectional study was conducted from January to February 2022 in Sewon District, Bantul Regency. Data were collected using a questionnaire on 116 women of childbearing age who have children and have WhatsApp media. The sample size was calculated using the Raosoft Sample Size Calculator software with a 95% confidence level from 165 women of childbearing age. By using path analysis, it can be seen that perceived threat perception has a direct effect on contraceptive use behavior (b=1.26, 95% CI= 0.48 to 2.05, p=0.001). Perception of seriousness had an indirect effect on contraceptive use through perceived threat perception (b=2.14, 95% CI=1.12 to 3.15, p<0.001). Perceived severity had an indirect effect on contraceptive use through perceived threat perception (b=1.98, 95% CI=.93 to 3.04, p<0.001). Initiatives are needed to improve contraceptive use behavior. Furthermore, these findings can be considered in the formulation of health care policies to overcome problems that hinder the use of contraception by women of childbearing age.